GATE 2024 Civil Engineering - G. K. Publications (New Delhi, G K Publications (P) Ltd, 2023)
"GKP's Prep Series: GATE 2024 : Civil engineering , which is prepared by renowned faculties who are subject matter experts, is your best bet to be GATE READY! The entire book has been revised and updated as per latest exam syllabus. It is divided into units, chapters and further segmented into topics. The topic-wise analysis of previous year's papers and weightage of each topic is given in each chapter. The questions given with the unit have detailed answers, supported by in-depth explanations and diagrams. The book also includes well explained sections on General Aptitude and Engineering Mathematics other than Electronics and communications. It also includes more than 2800 MCQs and NTQs, last four years' GATE Solved papers of 2020-2023. Additionally students can avail GATE previous year solved papers from 2015-2019 through our online platform. Features: Comprehensive theory with concepts Ample questions supplemented with solutions and diagrams Thoroughly revised and updated as per new syllabus 3 full-length mock tests."
Keywords: GATE 2024 I Civil Engineering